Effect of close-up metabolizable protein supply on colostrum yield, composition, and immunoglobulin G concentration and associations with prepartum metabolic indicators of Holstein cows - T.A. Westhoff; A. Abuelo; T.R. Overton; M.E. Van Amburgh; S. Mann (Journal of Dairy Science)
ABSTRACT: The prepartum diet as well as individual metabolic status of the cow influences colostrum parameters. The objectives of this study were to (1) investigate the effect of increasing prepartum dietary MP supply on colostrum yield, composition, and IgG concentration, and (2) identify prepartum metabolic indicators associated with these outcomes. Multiparous Holstein cows (n = 96) were blocked by expected calving date and randomly assigned to 1 of 2 prepartum diets formulated to contain a control (85 g of MP/kg of DM; 1,175 g of MP/d) or high (HI; 113 g of MP/kg DM; 1,603 g of MP/d) level of MP starting at 28 d before expected calving. Both prepartum diets were formulated to supply Met and Lys at an equal amount of 1.24 and 3.84 g/Mcal ME, respectively. Metabolic indicators were determined in serum (albumin, glutamate dehydrogenase, cholesterol, aspartate transaminase, total protein, total bilirubin, and IgG) or plasma (Ca, glucose, fatty acids, BHB, and urea nitrogen) twice weekly in a subset of cows (n = 60). Colostrum was harvested at 3.6 ± 2.4 h from calving and yield as well as concentrations of IgG, fat, protein, and Ca were determined. Cows were retrospectively grouped based on the typical volume of colostrum needed for 2 colostrum meals (<6 or ≥6 kg), IgG concentration (<100 or ≥100 g/L), as well as the median concentrations of fat (<4.4% or ≥4.4%), protein (<16.5% or ≥16.5%), Ca (<0.21% or ≥0.21%), and total colostrum ME (<8.65 or ≥8.65 Mcal). Data were analyzed using mixed effects ANOVA, with repeated measures where applicable. Feeding HI tended to increase colostrum yield in cows entering parity 2 (9.4 vs. 7.2 ± 0.9 kg), but treatment did not affect yield from cows entering parity ≥3 (5.1 vs. 6.4 ± 1.0 kg). Supply of MP did not affect concentrations of IgG, fat, protein, or Ca. Cows that produced ≥6 kg versus those producing <6 kg of colostrum had lower plasma concentrations of glucose. Metabolic indicators were not associated with IgG group. Colostrum fat ≥4.4% was associated with cows having lower prepartum concentrations of glucose, total protein, albumin, and aspartate transaminase activity. Colostrum protein ≥16.5% was associated with lower circulating serum IgG and elevated cholesterol. Elevated glucose as well as lower cholesterol and BHB concentrations were associated with colostrum Ca ≥0.21%. Further, higher albumin and fatty acids as well as lower glucose concentrations were associated with a greater colostrum energy output. In conclusion, increasing prepartum MP supply tended to increase colostrum yield in cows entering parity 2, but did not affect the composition or IgG concentration. The observed associations between metabolic indicators and colostrum parameters suggest that slight adjustment in metabolism during late gestation might be necessary to support colostrogenesis, but the causality of these relationships should be considered.